O sertão vai para o Além-Mar : a relação centro e periferia e as fábricas de couro em Pernambuco nos setecentos - Medeiros, Tiago Silva (2009)
This thesis focuses on the economic relations in the interior of the Portuguese America, more specifically in Pernambuco Captancy in the 17th Century, concerning the discussion about center-periphery relationship and also the context of Brazilian colonial history. In addition, it portrays the exportations of leather to Portugal, their consequences in the Captaincy of Pernambuco and the businessmen involved in the trade and manufacturing of that product. In order to accomplish this work, manuscripts of Arquivo Histórico Ultramarino (Ultramarine Historical Archives), colonial narratives and maps of the mercantile loads have been used so that one can visualize that the manufacturing of leather and other products have provided a social and economical connection among Pernambuco, Recife as trade center, Olinda as administrative municipality and Portugal